Butterfly Species Diversity and Abundance at Govt. Holkar Science College Campus, Indore - Alone, Rakesh; Jat, Dharmendra (International Journal of Scientific Research in Biological Sciences, 2021)
A study on butterfly was carried out at Holkar Science College Campus, Indore District, Madhya Pradesh, India, during 2020 to 2021. A total of 51 butterfly species were recorded. Family Nymphalidae (21) dominates in the study area, followed by Pieridae (11), Lycaenidae (11), Papilionidae (05) with minimum members of Hesperiidae (03). Total larval food plants recorded from the campus are 41 belonging to different families. Hygrophylla aericulata were found most importance larval food plants as they supports the five pansies found here. The ratio of food plants and butterflies is near about 1:1. Plants of the Asteraceae family were more used by butterflies as nectar food plants. These findings are important with respect to butterfly diversity and abundance in planning conservation strategies in the area. The very common butterflies are Common jezebel, Common gull, Common emigrant, Mottled emigrant, Common grass yellow, Red Pierrot, Common castor, Chocolate pansy, Pale grass blue, Small grass jewel, Lemon pansy, Great egg fly, Danaid egg fly, Plain tiger and among very rare includes Lesser gul, Baronet, Grey pansy, Spot swordtail, Royal peacock, Commander, and Common wanderer. The study area is rich in butterfly diversity and further research could be conducted to obtained more details and documentation on butterfly diversity and abundance for the conservation and butterfly park.